Apakah Kepemilikan Publik dan Kontinjensi Berpengaruh terhadap Audit Report Lag dengan Reputasi KAP sebagai Pemoderasi? - Iyun Yusnita; Shinta Ningtiyas Nazar; Syafrizal Syafrizal (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2022)
This study aims to analyze the effect of public ownership and contingencies on audit report lag with KAP's reputation as moderating. This research uses associative quantitative research, where there is a relationship between 2 (two) or more variables. The type of data used is Panel Data, where the data consists of many years of research and consists of many companies. The data used is secondary data derived from the entity's annual report taken from the official website of the Indonesia Stock Exchange (IDX) and IDN Financials. The research population is the Non-Cyclical Consumer sector company for the 2016-2019 period with a total sample of 30 companies (Purposive Sampling Method). A total of 120 observational data were processed through the Eviews 9 application with the stages of Descriptive Statistics Test, Regression Model Test, Classical Assumption Test, Panel Data Regression Test and Hypothesis Testing. The results showed that the public ownership variable had no effect on audit report lag, contingency variables had no effect on audit report lag, the KAP reputation variable could not moderate the effect of public ownership and contingency effects on audit report lag.